READING HABIT OF STUDENTS IN GANDHINAGAR CITY: A CASE STUDY (International Journal of Food and Nutritional Sciences, 2022)
Reading habit is the most effective way of developing reading skill among youth and it can improve their academic performances and become better people in the society. The study title “Reading habit of students in Gandhinagar City : A Case study ” this study was conducted among students form Gandhinagar city using simple random sampling as the sampling technique. The data was analyzed using tables and simple statistics. The findings revealed that most students are female (56%). Most students always reads textbooks, they spend 1 – 2 hours reading. They further claimed that watching television, chatting through social networks had negative influence on their academic performance. Therefore, spending more time reading, library time should be provide in their school timetable these can improve the students reading habit and academic performance.